The employability model for the multiple intelligence of people with epilepsy - Alimin, Nur Sofia Nabila (2014)
The objectives of this study are to identify the intelligence profiles of People with Epilepsy (PWE) based on Ability Test in Epilepsy, ATIE© (2008), the PWE’s type of intelligence and their employment status, to develop an Employability Model which involves significant factors that lead to high employability and to determine the significant factors for PWE high employability. The data used in this study are the integration with the data from the previous study by Awang in 2012 on the multiple intelligence of PWE in Malaysia. Awang (2012) used 166 data from Neurology Department, Kuala Lumpur General Hospital (HKL). However, the sample in this study consists of outpatients at the Neurology Department HKL and Hospital Sultanah Aminah (HSA), Johor Bahru. The sample size from HKL are 148 patients and from HSA are 67 patients that made up a total sample of 215 patients. Two main methods used in this study are descriptive statistics and logistic regression analysis. The descriptive statistics shows that the intelligence profiles that are mostly possessed by PWE are mediocre level of musical intelligence (40.5%), high level of kinesthetic intelligence (40.5%), high level of math/logic intelligence (38.6%), high level of spatial intelligence (41.4%), mediocre level of linguistic intelligence (38.1%), high interpersonal intelligence (57.2%), high level of intrapersonal intelligence (58.6%) and mediocre level of naturalistic intelligence (41.4%). From the logistic regression method, two models were developed which are the full model and the Employability Model. As a conclusion, the Employability Model build shows eleven significant factors that increase the chances for the PWE to be employed namely gender, marital status, education background, age of the respondents, onset age, musical intelligence, kinesthetic intelligence, logic/math intelligence, spatial intelligence, intrapersonal intelligence and naturalistic intelligence